2012
DOI: 10.1038/nature11600
|View full text |Cite
|
Sign up to set email alerts
|

Principles for designing ideal protein structures

Abstract: Unlike random heteropolymers, natural proteins fold into unique ordered structures. Understanding how these are encoded in amino-acid sequences is complicated by energetically unfavourable non-ideal features—for example kinked α-helices, bulged β-strands, strained loops and buried polar groups—that arise in proteins from evolutionary selection for biological function or from neutral drift. Here we describe an approach to designing ideal protein structures stabilized by completely consistent local and non-local… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
697
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 540 publications
(712 citation statements)
references
References 71 publications
14
697
1
Order By: Relevance
“…Researchers from the same laboratory as Koga et al had previously reported 4 the impressive preparation of Top7 -a 93-residue α/β-protein designed to adopt a tertiary structure not found in nature, and which incidentally satisfies the newly established design principles 1 . But the success of Koga and colleagues' protocol, and its incorporation of negative design, is a big step forward compared with that earlier work.…”
Section: St E P H E N J S M a R T Tmentioning
confidence: 99%
See 2 more Smart Citations
“…Researchers from the same laboratory as Koga et al had previously reported 4 the impressive preparation of Top7 -a 93-residue α/β-protein designed to adopt a tertiary structure not found in nature, and which incidentally satisfies the newly established design principles 1 . But the success of Koga and colleagues' protocol, and its incorporation of negative design, is a big step forward compared with that earlier work.…”
Section: St E P H E N J S M a R T Tmentioning
confidence: 99%
“…It would be immensely useful to be able to predict native structures from amino-acid sequences, but our understanding of how such sequences determine the three-dimensional arrangements of proteins is limited. On page 222 of this issue, Koga et al 1 describe a set of rules that relate secondary protein-structure patterns -α-helices and β-sheets -to tertiary features. They also show how these principles can be used to design amino-acid sequences that fold into predefined topologies.…”
Section: B I R T E H ö C K E Rmentioning
confidence: 99%
See 1 more Smart Citation
“…More general methods such as RosettaDesign 13 are based on minimizing an effective energy function, which has been, for large parts, derived from molecular mechanics force fields 4 . It has been shown that RosettaDesign can achieve high success rates for idealized target structures 10 . However, success rates of automated design with common targets has remained low 14,15 .…”
mentioning
confidence: 99%
“…These progresses have been driven by underlying computational or rule-based design methods, which can be stringently calibrated through the de novo design of amino acid sequences that fold into desired three-dimensional structures 4,[8][9][10] . In this regard, rule-based designs have attained some remarkable successes 7,11,12 , albeit limited to particular types of target structures or structure motifs.…”
mentioning
confidence: 99%